Communication Strategy of the Padang City Tourism Office in Building a Creative Village - Umi Chalzhum Caniago (GLOBAL SCIENTS PUBLISHER, 2024)
Communication strategies are needed to produce a communication process that can be understood by the recipient of information in achieving goals. Therefore, the organization / or company must develop the right communication strategy so that the message conveyed to the target object can be understood properly. research was conducted to analyze the performance of the Tourism Office in implementing the strategy of the Creative Village, especially in the aspect of communication, because there are still many villages that do not participate in the activities of the Creative Village, this is due to the lack of understanding of the Village community about what, the purpose, the why and the elements of the Creative Village itself. Therefore, the thesis that the researcher made was entitled